Cell-Based Therapy in TBI: Magnetic Retention of Neural Stem Cells in Vivo. Issue 6 (June 2016) - Shen, Wei-Bin; Plachez, Céline; Tsymbalyuk, Orest; Tsymbalyuk, Natalya; Xu, Su; Smith, Aaron M.; Michel, Sarah L. J.; Yarnell, Deborah; Mullins, Roger; Gullapalli, Rao P.; Puche, Adam; Simard, J. Marc; et al.
Stem cell therapy is under active investigation for traumatic brain injury (TBI). Noninvasive stem cell delivery is the preferred method, but retention of stem cells at the site of injury in TBI has proven challenging and impacts effectiveness. To investigate the effects of applying a magnetic field on cell homing and retention, we delivered human neuroprogenitor cells (hNPCs) labeled with a superparamagnetic nanoparticle into post-TBI animals in the presence of a static magnetic field. We have previously devised a method of loading hNPCs with ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles Molday ION Rhodamine B (MIRB™). Labeling of hNPCs (MIRB-hNPCs) does not affect hNPC viability, proliferation, or differentiation. The 0.6 tesla (T) permanent magnet was placed ~4 mm above the injured parietal cortex prior to intracarotid injection of 4 × 10 4 MIRB-hNPCs. Fluorescence imaging, Perls' Prussian blue histochemistry, immunocytochemistry with SC121, a human-specific antibody, and T2-weighted magnetic resonance imaging ex vivo revealed there was increased homing and retention of MIRB-hNPCs in the injured cortex as compared to the control group in which MIRB-hNPCs were injected in the absence of a static magnetic field. Fluoro-Jade C staining and immunolabeling with specific markers confirmed the viability status of MIRB-hNPCs posttransplantation. These results show that increased homing and retention of MIRB-hNPCs post-TBI by applying a static magnetic field is a promising technique to deliver cells into the CNS for treatment of neurological injuries and neurodegenerative diseases.